43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-538
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Contour Crafting - A Novel Technique for ISRU-Based Habitat Development

Abstract: and Michael R. Fiske5Morgan Research Colporation, Huntsville. AL, 35805 As the nation prepares to return to the hfoon, it is apparent that the viability of long duration visits with appropriate radiation shieldingkrew protection, hinges on the development of Lunar structures, preferably in advance of a manned landing, and preferably utilizing in-situ resources. Contour Crafting is a KSC-patented technique for automated development of terrestrial concrete-based structures. The process is relatively fast, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…In order for this step of human colonisation to become a reality, engineers back on earth are assigned the highly challenging task in finding efficient and cost-effective ways to build structures that will be able to support life and scientific activity whilst resisting Martian/Lunar environmental threats such as micro-meteoroid impacts, solar and cosmic radiation, intense temperature loads, etc. Numerous studies are available in the literature proposing and engineering ways in fabricating habitats by either dwelling caves underneath the surface or via the concept of In-Site Resource Utilisation (ISRU) to use indigenous materials, readily available onsite to build such habitat structures (8)(9)(10).…”
Section: -Introductionmentioning
confidence: 99%
“…In order for this step of human colonisation to become a reality, engineers back on earth are assigned the highly challenging task in finding efficient and cost-effective ways to build structures that will be able to support life and scientific activity whilst resisting Martian/Lunar environmental threats such as micro-meteoroid impacts, solar and cosmic radiation, intense temperature loads, etc. Numerous studies are available in the literature proposing and engineering ways in fabricating habitats by either dwelling caves underneath the surface or via the concept of In-Site Resource Utilisation (ISRU) to use indigenous materials, readily available onsite to build such habitat structures (8)(9)(10).…”
Section: -Introductionmentioning
confidence: 99%
“…Investment casting molds and cores have been printed in sand [343] and large structures have been printed in clay and concrete [171] [173]. Research to print Lunar and Martian habitats using locally available materials such as lunar regolith is also underway [172]. Various AM processes have been used to print edible items such as chocolate, sugar, frosting, pasta, spreads, cheese, scallop puree, ground beef, egg whites, insect powders, and an entire pizza.…”
Section: Materials Choicementioning
confidence: 99%
“…the Moon, Mars etc. ), that would function autonomously and utilise indigenous materials as feedstock [8][9][10][11]. Previous studies have demonstrated that the application of a Powder Bed Fusion 3D printing process can manufacture structures/components from multi component ceramics that closely simulate Lunar and Martian regolith [12,13].…”
Section: Introductionmentioning
confidence: 99%